Circadian Factor BMAL1 in Histaminergic Neurons Regulates Sleep Architecture - Wisden,W; Yu,X; Zecharia,A; Zhang,Z; Yang,Q; Yustos,R; Jager,P; Vyssotski,AL; Maywood,ES; Chesham,JE; Ma,Y; Brickley,SG; et al. (Current Biology, 2014)
Circadian clocks allow anticipation of daily environmental changes [ 1 ]. The suprachiasmatic nucleus (SCN) houses the master clock, but clocks are also widely expressed elsewhere in the body [ 1 ]. Although some peripheral clocks have established roles [ 1 ], it is unclear what local brain clocks do [ 2, 3 ]. We tested the contribution of one putative local clock in mouse histaminergic neurons in the tuberomamillary nucleus to the regulation of the sleep-wake cycle. Histaminergic neurons are silent during sleep, and start firing after wake onset [ 4–6 ]; the released histamine, made by the enzyme histidine decarboxylase (HDC), enhances wakefulness [ 7–11 ]. We found that hdc gene expression varies with time of day. Selectively deleting the Bmal1 (also known as Arntl or Mop3 [ 12 ]) clock gene from histaminergic cells removes this variation, producing higher HDC expression and brain histamine levels during the day. The consequences include more fragmented sleep, prolonged wake at night, shallower sleep depth (lower nonrapid eye movement [NREM] δ power), increased NREM-to-REM transitions, hindered recovery sleep after sleep deprivation, and impaired memory. Removing BMAL1 from histaminergic neurons does not, however, affect circadian rhythms. We propose that for mammals with polyphasic/nonwake consolidating sleep, the local BMAL1-dependent clock directs appropriately timed declines and increases in histamine biosynthesis to produce an appropriate balance of wake and sleep within the overall daily cycle of rest and activity specified by the SCN.